1996
DOI: 10.1002/actp.1996.010470606
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of ethyl cyanoacrylate and ethylene in the presence of zinc chloride or trifluoroacetic acid as complexing agent

Abstract: The free radical copolymerization of ethene and ethyl cyanoacrylate (ECA) in the presence of Lewis and Brensted acids has been studied in detail. Both trifluoroacetic acid (TFA) and ZnClz.Et,O were found to be useful complexing agents for synthesizing highly alternating copolymers of olefins and ECA. The influence of the complexing agents was quantified by determination of the copolymerization parameters r, of ECA for ECA/ET copolymerization. The synthesized copolymers showed unusual thermal behavior with rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…For radical copolymerizations, there have been several reported methods for enhancing the copolymerizations. One of the most effective methods is to add strong Lewis acids, such as AlR n Cl 3− n , BF 3 , SnCl 4 , , ZnCl 2 , etc., for increasing the copolymerizability of nonpolar olefins with polar monomers, such as acrylonitrile, acrylates, and methacrylates. Although the detailed mechanisms of these copolymerizations have not yet been completely clarified, the enhanced reactivity seems to be due to the coordination of the Lewis acids to the carbonyl groups of the acrylic monomer and its growing radical species, which decreases the electron density of the vinyl group and the growing radical to enhance the cross-propagation to the relatively electron-rich nonpolar olefin monomer and its propagating radical species, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For radical copolymerizations, there have been several reported methods for enhancing the copolymerizations. One of the most effective methods is to add strong Lewis acids, such as AlR n Cl 3− n , BF 3 , SnCl 4 , , ZnCl 2 , etc., for increasing the copolymerizability of nonpolar olefins with polar monomers, such as acrylonitrile, acrylates, and methacrylates. Although the detailed mechanisms of these copolymerizations have not yet been completely clarified, the enhanced reactivity seems to be due to the coordination of the Lewis acids to the carbonyl groups of the acrylic monomer and its growing radical species, which decreases the electron density of the vinyl group and the growing radical to enhance the cross-propagation to the relatively electron-rich nonpolar olefin monomer and its propagating radical species, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has to be clearly stated that only alternating an−et sequences, which may be interrupted by short an poly-ades (deviation from the strict alternation) and absolutely no et sequences are formed under the given polymerization conditions; contrarily, the acid-free AN−ET copolymerization at elevated pressure leads to copolymers, where both longer an and et sequences occur (cf. refs and ).…”
Section: Resultsmentioning
confidence: 98%
“…As has already been demonstrated, the complexation of the acceptor comonomer acrylonitrile (AN) with Lewis acids (i.e., ZnCl 2 ·Et 2 O, EtAlCl 2 ) influences the comonomer reactivities and the copolymerization parameters. ,,, Surprisingly, it was found that bipolymers with periodic comonomer sequences, ideally alternating copolymers of electron donor and acceptor comonomers, can be also synthesized in the presence of strong organic Brönsted acids. ,, This is reflected from the experimental and analytical data of a set of copolymerizations of ethene and acrylonitrile in the presence of different acids carried out at the same reaction conditions (Table , nos. 2−8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperlich and Eisenbach overcame this issue by employing CF 3 CO 2 H or ZnCl 2 .OEt 2 as complexing agents in the copolymerization of ethylene with ethyl 2-cyanoacrylate to form alternating copolymers [78]. Copolymerizations were carried out in a pressure reactor using DCHPC as initiator, with reaction components added together at −80 °C before being heated to 40 °C and maintained at that temperature for 15 h. The concentration of complexing agent was found to have a significant influence on the degree of alternation of the copolymer.…”
Section: Conventional (Non-living) Radical Polymerizationsmentioning
confidence: 99%